2007
DOI: 10.1152/ajplung.00131.2007
|View full text |Cite
|
Sign up to set email alerts
|

Fine airborne urban particles (PM2.5) sequester lung surfactant and amino acids from human lung lavage

Abstract: Kendall M. Fine airborne urban particles (PM2.5) sequester lung surfactant and amino acids from human lung lavage. Am J Physiol Lung Cell Mol Physiol 293: L1053-L1058, 2007. First published July 6, 2007; doi:10.1152/ajplung.00131.2007.-Components of surfactant act as opsonins and enhance phagocytosis of bacteria; whether this process occurs with atmospheric fine particles has not been shown. We have studied the interactions of fine particles (urban PM2.5) and surfactant removed from normal human lungs by lav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 38 publications
4
35
0
1
Order By: Relevance
“…This again corresponds with work where the amino acids valine and leucine were demonstrated to associate readily with PM 2.5 [7]. The results suggest that ENP agglomeration is driven by LDHA and LDHB as no LDH was found to be associated in samples 7 -9 which demonstrated very low aggregation.…”
Section: Discussion (A) Engineered Nanoparticle Agglomeration In Condsupporting
confidence: 84%
See 1 more Smart Citation
“…This again corresponds with work where the amino acids valine and leucine were demonstrated to associate readily with PM 2.5 [7]. The results suggest that ENP agglomeration is driven by LDHA and LDHB as no LDH was found to be associated in samples 7 -9 which demonstrated very low aggregation.…”
Section: Discussion (A) Engineered Nanoparticle Agglomeration In Condsupporting
confidence: 84%
“…While these motifs were found in a wide range of human proteins, none of the 18 were found in the infrequently associating proteins, suggesting a role for these sequences in associating with the polystyrene ENPs. When the properties of the amino acids within these conserved sequences were considered, the majority of the conserved motifs (94%, n ¼ 17) were noted to contain hydrophobic amino acids (leucine, isoleucine, methionine and valine), two of which (leucine and valine) were previously demonstrated to interact with PM 2.5 [7]. We therefore consider that the hydrophobic effect and weak van der Waals forces dominate the interactions between the proteins and polystyrene ENPs.…”
Section: Discussion (A) Engineered Nanoparticle Agglomeration In Condmentioning
confidence: 99%
“…Despite early evidence of particle coronas in the lung identified using newly developed atomic and molecular scale techniques [11], the biological interface remains the least understood aspect about nanoparticles, and classification systems to characterise the outermost layers of the bio-nano interface, i.e., those biological signatures that are available to engage endogenous cellular machinery, are absent. By far the most studied component of the corona is the protein composition [7,12], but lipids, sugars and other species likely also play a role [13][14][15]. Thus, despite the importance of the bio-nano interface, and the fact that it potentially holds the key to both safe implementation of nanotechnologies and nanomedicine, efforts to characterize it are surprisingly scarce [16].…”
Section: The Bio-nano Interface -Providing a Biological Identity To Nmentioning
confidence: 99%
“…The occupational setting is now considered as the most likely exposure route to engineered nanoparticles, but medical formulations may result in a wider population exposure [12]. The contribution of exposure to ultrafine particles such as those from combustion processes, to respiratory and skin diseases as well as more insidious and complex pathologies such as cancer and cardiovascular dysfunction, is now becoming apparent [93][94][95].…”
Section: The Signalling Concept: Interaction Of Nanoparticles With Mamentioning
confidence: 99%
“…So far this interaction with surfactant has not been shown with NPs but it is likely to be similar. Surfactant lipids and proteins may adsorb to the surface of PM 2.5 particles, thereby eventually modulating the function of pulmonary surfactant (59). Similarly, Bakshi and colleagues have demonstrated that gold NPs sequester lung surfactant and may interfere with its normal function (6).…”
Section: Cell Barriers (Membranes)mentioning
confidence: 99%